De novo genome assembly of the cichlid fish Astatotilapia latifasciata reveals a higher level of genomic polymorphism and genes related to B chromosomes - Jehangir, Maryam [UNESP]; Ahmad, Syed F. [UNESP]; Cardoso, Adauto L. [UNESP]; Ramos, Erica [UNESP]; Valente, Guilherme T. [UNESP]; Martins, Cesar [UNESP] (Springer Nature, 2019)
Supernumerary B chromosomes (Bs) are accessory elements to the regular chromosome set (As) and have been observed in a huge diversity of eukaryotic species. Although extensively investigated, the biological significance of Bs remains enigmatic. Here, we present de novo genome assemblies for the cichlid fish Astatotilapia latifasciata, a well-known model to study Bs. High coverage data with Illumina sequencing was obtained for males and females with 0B (B−), 1B, and 2B (B+) chromosomes to provide information regarding the diversity among these genomes. The draft assemblies comprised 771 Mb for the B− genome and 781 Mb for the B+ genome. Comparative analysis of the B+ and B− assemblies reveals syntenic discontinuity, duplicated blocks and several insertions, deletions, and inversions indicative of rearrangements in the B+ genome. Hundreds of transposable elements and 1546 protein coding sequences were annotated in the duplicated B+ regions. Our work contributes a list of thousands of genes harbored on the B chromosome, with functions in several biological processes, including the cell cycle.
Keywords: Chromosome rearrangement; Cichlid fish; Extra chromosome; Genome evolution; Next-generation sequencing; Supernumerary chromosome